Nociceptive Sensory Neurons Mediate Inflammation Induced by Bacillus Anthracis Edema Toxin - Yang, Nicole J.; Neel, Dylan V.; Deng, Liwen; Heyang, Michelle; Kennedy-Curran, Angela; Tong, Victoria S.; Park, Jin Mo; Chiu, Isaac M. (Frontiers in Immunology, 2021)
Bacterial products are able to act on nociceptive neurons during pathogenic infection. Neurogenic inflammation is an active part of pain signaling and has recently been shown to impact host-pathogen defense. Bacillus anthracis Edema Toxin (ET) produces striking edema in peripheral tissues, but the cellular mechanisms involved in tissue swelling are not completely understood. Here, we find that nociceptive neurons play a role in ET-induced edema and inflammation in mice. Subcutaneous footpad infection of B. anthracis Sterne caused ET-dependent local mechanical allodynia, paw swelling and body weight gain. Subcutaneous administration of ET induced paw swelling and vascular leakage, the early phases of which were attenuated in the absence of Trpv1+ or Nav1.8+ nociceptive neurons. Nociceptive neurons express the anthrax toxin receptor ANTXR2, but this did not mediate ET-induced edema. ET induced local cytokine expression and neutrophil recruitment, which were dependent in part on Trpv1+ nociceptive neurons. Ablation of Trpv1+ or Nav1.8+ nociceptive neurons also attenuated early increases in paw swelling and body weight gain during live B. anthracis infection. Our findings indicate that nociceptive neurons play an active role in inflammation caused by B. anthracis and Edema Toxin to potentially influence bacterial pathogenesis.